말발굽 골이식과 Herbert 나사 및 초소형나사를 이용한 주상골 불유합의 치료 - 강호정(Ho-Jung Kang); 박훈(Hoon Park); 한수봉(Soo-Bong Hahn) (The journal of the Korean Orthopaedic Association, 2009)
목 적: 곱사등 변형이 동반된 주상골 불유합에서 골결손 부위를 정확히 측정하고 이식술을 시행하는 것이 이상적이나 골이식술만으로 3차원적으로 완벽한 해부학적 정복을 얻는 것은 쉽지 않다. 이에 본 연구는 주상골 불유합시 말발굽 골이식술 및 2개의 나사를 이용한 내고정술의 치료효과를 알아보고자 하였다. 대상 및 방법: 2001년 3월부터 2006년 1월까지 주상골 불유합으로 말발굽 골이식술 및 Herbert나사와 초소형 나사, 2개를 이용한 내고정술을 시행 받은 19예를 대상으로 하였다. 평균 연령은 30.5세였으며, 수상일로부터 수술일까지의 이환 기간은 평균 6.7년이었고 수술 후 추시기간은 평균 24개월이었다. 골절 부위는 요부 골절이 15예로 가장 많았으며, 원위 1/3골절이 4예였으며, 근위부 골절은 없었다. 수술은 1예에서 배측 도달법을 사용하였으며, 18예에서는 수장부 도달법을 사용하였다. 2예에서 분쇄골편 및 술 후 고정 불안정성으로 인해 1개의 K 강선을 추가적으로 사용하였다. 결 과: 전체19예의 환자 중 18예(95%)에서 골유합을 얻었고, 수술 후 유합까지의 평균기간은 13주였다. 수술 전 주상-월상각은 평균 65.2도에서 술 후 49.5도로 개선되었으며, 측방 주상골내 각은 술 전 43.5도에서 술 후 29.6도로 개선되었다. 최종 추시 시 임상 결과는 우수 3예, 양호 10예, 보통 6예의 결과를 보였다. 합병증으로는 임상증상이 없었던 불유합이 1예 있었고, 관절운동범위 제한이 4예 있었다. 결 론: 골 결손 및 곱사등 변형이 심한 주상골 불유합의 치료에 말발굽 골이식술 및 Herbert나사와 초소형 나사 고정술이 주상골의 해부학적 길이 및 형태를 유지하고, 이식골편의 이동을 막으면서 골유합을 얻을 수 있는 비교적 용이한 수술방법으로 사료된다. Purpose: Three dimensional anatomical reconstruction of an old scaphoid nonunion injury with a humpback deformity is not an easy procedure. The single interpositional bone graft technique has its limitation for accurate anatomic reconstruction. We report here on the effect of a cortical interpositional horse-shoe graft using two screws and a volar cancellous chip bone graft for the treatment of scaphoid nonunion with a humpback deformity or a miss-match fracture surface in scaphoid nonunion. Materials and Methods: We retrospectively reviewed nineteen patients who were treated for scaphoid nonunion using a cancellous chip bone graft and a cortical interpositional horse-shoe graft with 2 screws(a Herbert's screw and a mini screw). The mean follow up period was 24 months (range: 14-36 months). The mean age was 30.5 years (range: 17-52 years) and 18 patients were male and 1 patient was female. The mean period between injury and operation was 6.7 years (range: 1 to 30 years). The nonunion sites were located in the waist in 15 wrists and in the distal third in 4 wrists. The volar approach was used in 18 cases and the dorsal approach was used in 1 case. In 2 cases, one additional kirschner’s wire was used due to the instability of fixation. The clinical results were assessed by the criteria of Maudesley and Chen at the last follow-up. Results: Bony union was obtained in 18 (95%) cases. The average time for union was 13 weeks. There were improvements in the scapholunate angle (from 65.2 degrees to 49.5 degrees) and the intrascaphoid angle (from 43.5 degrees to 29.6 degrees). There are 3 cases with excellent results, 10 cases with good results and 6 cases with fair results. There was one complication. In 1 case, a nonunion gap was seen at 7 months after operation, but there were no clinical symptoms. Conclusion: A cortical interpositional horse-shoe graft using two screws and a cancellous chip bone graft for treating scaphoid nonunion with a humpback deformity or a large defect seems to be an encouraging procedure for regaining the normal anatomy of the scaphoid. KCI Citation Count: 1